Habitat fragmentation shapes natal dispersal and sociality in an Afrotropical cooperative breeder. Issue 1941 (23rd December 2020) - Cousseau, Laurence; Hammers, Martijn; Van de Loock, Dries; Apfelbeck, Beate; Githiru, Mwangi; Matthysen, Erik; Lens, Luc
Abstract : It remains poorly understood how effects of anthropogenic activity, such as large-scale habitat fragmentation, impact sociality in animals. In cooperatively breeding species, groups are mostly formed through delayed offspring dispersal, and habitat fragmentation can affect this process in two opposite directions. Increased habitat isolation may increase dispersal costs, promoting delayed dispersal. Alternatively, reduced patch size and quality may decrease benefits of philopatry, promoting dispersal. Here, we test both predictions in a cooperatively breeding bird (placid greenbul, Phyllastrephus placidus ) from an Afrotropical cloud forest archipelago. Males born in fragmented forest dispersed about 1 year earlier than those born in continuous forest. Contrary to females, males also started to reproduce earlier and mostly settled within their natal patch. Females only rarely delayed their dispersal for more than 1 year, both in fragmented and continuous forests. Our results suggest that early male dispersal and reproduction is jointly driven by a decrease in the value of the natal territory and an increase in local breeding opportunities in fragmented forest. While plasticity in dispersal strategies of cooperative breeders in response to anthropogenic change is believed to optimize reproduction-survival trade-offs, to what extent it shapes the ability of species to respond to rapid environmental change remains to be studied.